Perkawinan Beda Agama Menurut Fiqh - Nardoyo Amin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2006)
This study aims to examine the law of interfaith marriage in the perspective of Islamic fiqh. The differing views among scholars regarding the legal status of marriage between Muslims and non-Muslims is an ongoing debate. This study uses a qualitative method with a literature study approach, analyzing the arguments of the Qur'an, Hadith, and the views of fuqaha from various schools of thought. The results show that the majority of scholars prohibit marriage between Muslims and non-Muslims who are not people of the book, while some scholars allow Muslim men to marry women of the book. However, in the modern social context, a new approach has emerged that considers the aspects of maqashid Shariah and maslahat in looking at this issue. This study emphasizes that the law of interfaith marriage still requires contextual analysis to suit social realities without neglecting the principles of Shariah.